Models for Cell-Free Synthetic Biology: Make Prototyping Easier, Better, and Faster - Koch, Mathilde; Faulon, Jean-Loup; Borkowski, Olivier (Frontiers in Bioengineering and Biotechnology, 2018)
Cell-free TX-TL is an increasingly mature and useful platform for prototyping, testing and engineering biological parts and systems. However, to fully accomplish the promises of synthetic biology, mathematical models are required to facilitate the design and predict the behaviour of biological components in cell-free extracts. We review here the latest models accounting for transcription, translation, competition and depletion of resources as well as genome scale models for lysate-based cell-free TX-TL systems, including their current limitations. These models will have to find ways to account for batch-to-batch variability before being quantitatively predictive in cell-free lysate-based platforms.